Manuel Bandeira's legacy to the recognition of the modernist literary heritage (Ágora Journal, 2024)
Bringing literary criticism closer to studies on Brazilian cultural heritage, we analyze how Manuel Bandeira assumes, in the volume Crônicas da província do Brasil (1937), the place of authority in the exercise of criticism to legitimize the pantheon of authors that make up the consecrated memory of our literary heritage. The list of those elected constitutes a legacy of Bandeireira's modernist memory, responsible for feeding back the elaboration of the modernizing character of national art and culture. Thus, we pay attention both to the established position of Bandeira, a renowned poet since the publication of Libertinagem (1930), and to his consecrated place: member of the SPHAN advisory board since 1937 and member of the ABL since 1940, the writer occupies a prestigious place for define who can or cannot be part of this pantheon. Through the poet's chronicles, we propose to debate the reception of modern works and authors in the preservation of Brazilian modernist literary memory.
Keywords: crônicas da província do Brasil; history and literary criticism; literary heritage; Manuel Bandeira; modernist memory.